The Characteristic of Mubdil in Hajj (Analysis of Fiqh Al-Hadith) - Rahmi, Yulia; Ghazali, Norzulaili Mohd (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2021)
This paper explores the issue of mubdil in Badal Hajj. A mubdil is a person that performing the entire series of Hajj on behalf of a mubdal minhu (the person being replaced). According to hadith narrations, a mubdil is ideally a child or sibling of the mubdal minhu. However, in practice, Badal Hajj is often carried out by individuals with no familial ties to the mubdal minhu, and in some cases, the mubdil has no knowledge of the person they are replacing. Instances of responsibility misapplication and even fraudulent practices, such as performing Badal Hajj for multiple mubdal minhu, have also been reported. The practice of Badal Hajj is rooted in hadiths of the Prophet Muhammad, permitting to perform Hajj on behalf of others due to physical incapacity or death. This study employs the fiqh al-hadith method to examine these hadiths, analyzing them in relation to Quranic verses, other hadiths, and through both textual and contextual approaches. The findings reveal specific characteristics that a mubdil must possess to fulfill their responsibilities ethically and effectively. These characteristics, when realized, can minimize the misuse of responsibility and ensure the trustworthiness of Badal Hajj practices. This research contributes to the field of Islamic jurisprudence by providing a detailed framework for the ethical practice of Badal Hajj. It highlights the importance of maintaining trust and integrity in religious practices and offers methodological insights into analyzing hadiths in conjunction with contemporary challenges.